Rights-Based Approach to Maternal Health: Constitutionalizing Protection of Women's Reproductive Rights in Nigeria - Obadina, Ibrahim (Université d'Ottawa / University of Ottawa, 2023)
Maternal mortality in Nigeria is unacceptably high, accounting for 14 percent of global maternal deaths, thereby making it a global public health issue. Given that maternal mortality is essentially a women problem, it is a matter of justice and discrimination. In addition, significant regional disparities in maternal mortality exist within Nigeria, particularly between the northern and southern parts of the country. The maternal mortality ratio in the North is six to ten times greater than that of the South. The country's maternal mortality crisis occurs along regional and socioeconomic lines-the poorer northern Nigeria has a disproportionately higher maternal mortality ratio than the wealthier southern Nigeria. This thesis explores the disparities in maternal health across different regions in Nigeria from an intersectional perspective, taking into account economic, religious, cultural, rural, and urban differences. The study adopts intersectionality theory to examine how these factors intersect to impact maternal health outcomes in Nigeria. Furthermore, the thesis employs a functional comparative law approach, using India and South Africa as comparators, to assess how the constitutional courts of these countries have applied intersectional perspective to right to health. It highlights the importance of adopting an intersectional approach to understanding maternal health disparities in Nigeria, as it considers the multiple and interconnected factors that contribute to poor maternal health outcomes. This is particularly crucial in the Nigerian context, where maternal mortality rates remain high and access to quality maternal health services is limited, particularly in rural and underdeveloped regions. The comparative analysis of India and South Africa sheds light on how these countries have approached constitutionalizing the right to health and intersectionality in their courts. In South Africa, the Constitutional Court has played a crucial role in advancing the right to health and applying an intersectional perspective in its judicial decisions, leading to improvements in maternal health outcomes. In India, the Supreme Court has also played an important role in interpreting the right to health to include other associated factors, but its impact on maternal health outcomes remains limited, particularly in rural areas. The thesis concludes by advocating for constitutionalizing maternal health in Nigeria, through incorporation of the right to health in the Nigerian Constitution to ensure that this right is enforceable through the court processes. The study recommends that an adoption intersectional perspective in the implementation of maternal health policies and programs, in order to address the multiple and interconnected factors that contribute to maternal health disparities in Nigeria. The findings of this thesis contribute to the existing literature on maternal health and the right to health, and have important implications for policymakers and health practitioners working to improve maternal health outcomes in Nigeria and other developing countries. By incorporating an intersectional and comparative approach, the thesis provides a comprehensive understanding of the challenges and opportunities for constitutionalizing maternal health in Nigeria and highlights the need for a more nuanced and integrated approach to maternal health policy and practice.
Keywords: Maternal mortality; Regional disparities; Women's rights; Intersectionality; Nigeria; Comparative analysis